Efforts to Improve Employee Performance Through Career Adaptability and Perceived Organizational Support at Royal Prima Medan Hospital - Wiliam Wiliam; Syaifuddin Syaifuddin; Sopiyan Sopiyan (Universitas 17 Agustus 1945 Semarang, 2023)
The main objective of this research is to determine the direct influence of career adaptability and perceived organizational support on employee performance. The population and sample in this study were 120 permanent employees of the Royal Prima Medan Hospital. This type of research is quantitative. Data was obtained from distributing questionnaires. Data analysis uses Smart Pls, where it is hoped that the results of this research will be able to predict employee performance. The research results show that career adaptability and perceived organizational support directly affect employee performance. Then, perceived organizational support is assessed as the most dominant variable in influencing employee performance.